2016
DOI: 10.1088/0953-2048/30/1/015012
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of (Ba,K)Fe2As2tapes byex situPIT process using Ag-Sn alloy single sheath

Abstract: Instead of ordinal pure Ag, Ag-based Sn binary alloys (up to 7.5 at%Sn) with higher mechanical strength are used for the sheath material of ex situ powder-in-tube (PIT)-processed (Ba,K)Fe2As2(Ba-122) tapes. We found that the use of the Ag-Sn alloy enhances the densification and texturing of the Ba-122 core, resulting in higher transport, Jc. Moreover, the optimum heat treatment temperature for a high Jc can be lowered by around 100 °C due to the higher packing density of the Ba-122 core prior to the final heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…reported that the smoothness of the interface between the sheath and the core in (Ba,K)Fe 2 As 2 tape is significantly improved by using Ag-Sn binary alloy sheaths [64]. Using proper metal sheath, which is hard and stable against core material, uniform core shape in the wire can also be realized.…”
Section: Resultsmentioning
confidence: 99%
“…reported that the smoothness of the interface between the sheath and the core in (Ba,K)Fe 2 As 2 tape is significantly improved by using Ag-Sn binary alloy sheaths [64]. Using proper metal sheath, which is hard and stable against core material, uniform core shape in the wire can also be realized.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the high F values (>0.5) of previous BaK-122 and SrK-122 tapes were achieved using advanced techniques efficient for obtaining the c -axis orientation; (i) application of large uniaxial pressure (~4 GPa, which is 4 times larger than that in this work), (ii) application of hot-press technique, or (iii) use of Ag-Sn alloy sheath or Ag/stainless steel (SS) double sheath (which are harder than the pure Ag sheath used in this work). Thus, the comparison of F values between the BaNa-122 tape and various BaK-/SrK-122 tapes demonstrates that the use of BaNa-122 material is promising for obtaining a better c -axis orientation of the tape core.
Figure 5Orientation factor F of BaK-122 11,15,25,30,31 , SrK-122 14,16,32 , and BaNa-122. Several F values were calculated using the XRD patterns given in the references.
…”
Section: Discussionmentioning
confidence: 92%
“…Orientation factor F of BaK-122 11,15,25,30,31 , SrK-122 14,16,32 , and BaNa-122. Several F values were calculated using the XRD patterns given in the references.…”
Section: Discussionmentioning
confidence: 99%
“…Among all IBSs, 122-type compounds such as (Ba,K)Fe 2 As 2 have the best transport J c [15]. (Ba,K)Fe 2 As 2 (Ba-122), known as a 122-type IBS, has been widely studied because of its great potential for high-field magnet application [16][17][18][19]. For practical purpose, the preparation of wires and tapes is particularly important, and the transport J c is an important indicator of the performance of wires and tapes.…”
Section: Introductionmentioning
confidence: 99%